Regional Economic Outlook, April 2020, Middle East and Central Asia. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2020)
Countries of the Middle East and Central Asia region have been hit by two large and reinforcing shocks, resulting in significantly weaker growth projections in 2020. In addition to the devastating toll on human health, the COVID-19 pandemic and the plunge in oil prices are causing economic turmoil in the region, with fragile and conflict affected states particularlyhard-hit given already large humanitarian and refugee challenges and weak health infrastructures. The immediate priority for policies is to save lives with needed health spending, regardless of fiscal space, while preserving engines of growth with targeted support to households and hard-hit sectors. In this context, the IMF has been providing emergency assistance to help countries in the region during these challenging times. Further ahead, economic recoveries should be supported with broad fiscal and monetary measures where policy space is available, and by seeking external assistance where space is limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet